Youth Perception and Readiness for Organ Donation: A Survey-Based Study in Colleges of Ahmadabad District (International Journal of Food and Nutritional Sciences, 2023)
The study investigates awareness, perception, and willingness to donate organs in students through a sample of 70 students. A descriptive-analytical approach was adopted, and a structured questionnaire was the primary data collection tool. The questionnaire contained Likert-scale and demographic questions regarding awareness, willingness, cultural beliefs, and perceptions of social responsibility. Data were analyzed through Pearson correlation, Chi-square tests, and independent t-tests using SPSS. Findings showed that awareness of organ donation was statistically nonsignificantly and weakly correlated with willingness to register as a donor. Cultural beliefs were also not significant in determining willingness, with a linear trend present. No statistically significant gender differences in perceptions were found, indicating homogeneous attitudes among both male and female respondents. The findings point to gaps in awareness and registration as donors. The study proposes targeted awareness campaigns and education interventions to encourage positive donor attitudes.